Love of Money, Pengetahuan Kewirausahaan dan Minat Mahasiswa Akuntansi Berwirausaha - Yandini Eka Putri, Ni Putu; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2022)
This study aims to obtain empirical evidence regarding the effect of love of money and entrepreneurial knowledge on accounting students' interest in entrepreneurship. The research was conducted at the Accounting Study Program, Faculty of Economics and Business, Udayana University. The analysis technique used is multiple linear regression analysis. Based on the results of the distribution of the questionnaire obtained a sample of 89 student respondents. The results of the analysis show that love of money and knowledge of entrepreneurship have a positive effect on the interest of accounting students in entrepreneurship. The higher the level of love of money and entrepreneurial knowledge possessed by individuals, the greater the interest of accounting students in entrepreneurship Keywords: Love of Money; Entrepreneurial Knowledge ; Entrepreneurial Interest